Hydrocity: An International Collaborative Urban Lab between Manchester and Riga - Loris Rossi; Eamonn Canniffe; Matthew Quayle; Catalina Ionita (Environmental Science and Sustainable Development, 2025)
The Contextual Urbanism Lab at Manchester School of Architecture explores and develops future Urban Design Visions and engages in collaborative design work with other schools of architecture. In the 2023-24 academic year design work was undertaken in collaboration with students from the Latvian Riseba University of Applied Sciences, Faculty of Architecture and Design (Riseba FAD) for the repurposing of Kipsala Island, located on the west bank of the River Daugava in Riga and for the “Wirral Waters” regeneration area in Birkenhead (U.K). Through these design projects and the international experience, the students gained a full understanding of the opportunities presented by their sites to develop proposals for the reinvention of new, distinctive, and sustainable waterside districts at the heart of historic European cities. Having identified a site and personal manifesto, students were asked to test their ideas against their specific conditions. This detailed analysis led to comparative studies developed in both schools. The findings, contingent upon the different sizes and structures of the two schools, established a series of parameters to frame both the student and teacher research and raised questions on how the methods inherent in design synthesis highlighted a path towards either a professional or academic trajectory.